E-MONEY DITINJAU DARI DIMENSI MAQĀṢID AL-SYARĪ’AH - Muhammmad Noor Sayuti; Wijaya Wijaya (AL-QARDH, 2018)
The increasing popularity of technology-based pasyment system substanstially changes conventional payment system design from cash payment system to non-cash payment system. Gradually, the expansion is impressive enough to change paradigm of economist in micro-transaction settlement, as well as becoming the root of Less Cash Society spirit creation.One of the instruments of non-cash payment which has been a trend today is E-money.It is an electronic-based non-cash payment. Some studies showed that there was a positif impact to monetery policy earned from this trend, its influence in the level of velocity of money and the effort to reduce the use of cash payment as an effort to hold inflation flow. The purpose of this study is to find out maqāṣid al-syarī’ah dimension, which is a philosophical study about the real purpose of Syariat Islam. In this study, the data was analyzied by Qualitative-normative approach using inductive-analysis method. Maqāṣid al-syarī’ah dimension was observed using the theory of maṣlahah principle as a tool of analysis. It aimed to find out the advantage of e-money either in conventional economic concept or Islam concept, which is the aspect of utility and maṣlahah. Maṣlahah has become part of integration in studying Maqāṣid al-syarī’ah. It's due to the real meaning ofmaṣlahah is implement the purpose of syara’ as an effort in developing human life generally for now and hereafter. By observing maṣlahah principle toward e-money products including its derivative products which have become a trend these days, so it shows that the products of e-money only benefits the secular dimension. Precision in considering maṣlahah is indeed essential as extracting the ukhrawi dimension which has the same purpose with syariah principles, considering it e-money has the potential to completeness choice of product for sharia financial institution.